Photoelectrocatalytic degradation of p-chloronitrobenzene by g-C3N4/TiO2 nanotube arrays photoelectrodes under visible light irradiation. (March 2021) - Ma, Bingrui; Yu, Naling; Xin, Shuaishuai; Xin, Yanjun; Zhang, Chunlei; Ma, Xiaoming; Gao, Mengchun
Abstract: As a typical refractory pollutant, p -chloronitrobenzene ( p -CNB) from industrial wastewater poses a serious threat to the aquatic environment safety and human health. The photoelectrocatalytic (PEC) technology is regarded as a promising and cleaner approach for p -CNB removal. Therefore, the graphitic carbon nitride (g-C3 N4 ) modified TiO2 nanotube arrays (g-C3 N4 /TNAs) were prepared as the photoelectrodes for p -CNB degradation. The PEC degradation efficiency for p -CNB by g-C3 N4 /TNAs (0.00484 min −1 ) was much higher than that by bare TNAs (0.00135 min −1 ) under visible light. The g-C3 N4 /TNAs photoelectrodes exhibited excellent visible-light response, efficient charges separation and high redox potentials of electron/hole, which was favorable for p -CNB degradation. The radical scavenging experiments indicated that both reductive electrons and oxidized species (holes and ·OH) played crucial roles simultaneously during the dechlorination process, whereas the mineralization of p -CNB mainly depended on the photo-generated holes and ·OH. The degradation pathways of p -CNB were proposed through GC/MS spectra. The acute toxicity, bioaccumulation factor and mutagenicity of identified intermediates were reduced after PEC degradation by g-C3 N4 /TNAs photoelectrodes. The Z-scheme g-C3 N4 /TNAs provided an efficient approach for simultaneous dechlorination and mineralization of refractory pollutants. Graphical abstract: Image 1 Highlights: Z-scheme g-C3 N4 /TNAs reduced recombination of photo-generated electron-hole pairs. g-C3 N4 /TNAs exhibited high PEC degradation for p -CNB under visible light. Reductive electrons played crucial roles during the dechlorination process. The degradation pathways of p -CNB and its intermediates toxicity was analyzed.